AIVAZOVSKY'S CREATIVITY IN THE STATE MUSEUM OF ART OF UZBEKISTAN - Karimov Elyor (American Journals Publishing, 2025)
This article examines the creativity of Ivan Aivazovsky, his works about sea, as well as the technique he used to paint, which Russian artists and poets he influenced, and others. In addition, Aivazovsky traveled to some countries owing to his work, where he studied in order to achieve his goals and achievements. In particular, in the first decades of the 19th century, new trends and styles began to emerge in Russia one after another. At the beginning of this century, romanticism began to emerge on the basis of classicism. At the same time, this article also talks about the famous Russian artists of this period, Karl Bryullov and other artists.
Keywords: Uzbekistan, museum, Russian, painting, traveler, Aivazovsky, marine(sea).